Out come of haemodialysis in Acute Renal Failure Due to malaria: A single Centre Study - Munib, Syed; Jamal, Syed Sheraz (Journal of Postgraduate Medical Institute, 2011)
This study was conducted to find out the outcome of haemodialysis in patients with acute renal failure secondary to malaria. This study was conducted at DTH DIKhan, from Janauary to December 2004. Patients with acute renal failure secondary to malaria, not responding to fluid challenge and frusemide for twenty four hours and requiring haemodialysis were finally selected for the study. All these patients were haemodialysed after the requisite workup. Standard antimalarial therapy was continued during haemodialysis. in acute renal failure complicating malaria, early referral and early haemodialysis has good results in reducing mortality. Haemodialysis along with active treatment with antimalarial has an excellent response in these patients if administered timely.